Squeezing deformation control during bench excavation for the Jinping deep soft-rock tunnel. (October 2020) - Zhang, Chuanqing; Cui, Guojian; Zhang, Yang; Zhou, Hui; Liu, Ning; Huang, Shuling
Highlights: Stability problems caused by lower bench excavation were analysed. A new support system controlling squeezing deformation was proposed during the lower bench excavation of the headrace tunnel. Polar coordinate description methods for the maximum displacement and associated position were presented. Abstract: Jinping II hydropower station in Sichuan Province, China, is one of the largest tunnel groups in the world. The tunnel was excavated using bench excavation with a top heading and a bench. Severe squeezing problems were reported immediately after the excavation of the top heading when crossing the chlorite schist stratum at Ch.1+537 m. Squeezing deformation could last for a long period during tunnelling, similar to the problem of rockburst reported in the marble stratum distributed in the middle and east of the headrace tunnels. One year after the top heading excavation, the profile of the top heading still violated the profile tolerance and had to be reshaped due to the large convergence. A new support scheme was proposed to ensure the stability of the surrounding rock mass and control the excessive squeezing deformation during the bench excavation. For this, laboratory triaxial tests were first conducted under saturated and dry conditions to acquire the mechanical properties of chlorite schist. Then, the mechanical parameters of intact and damaged surrounding rock mass were determined using Hoek empirical estimation and a displacement inversion method, respectively. Next, initial support design was re-reviewed and evaluated based on the field displacement measurements, and the potential for squeezing in the overstressed rock mass was estimated. Thereafter, 10 supplementary support schemes were proposed using the numerical method in combination with laboratory data and field observations. Finally, the optimised support scheme was selected based on the results of comparative analysis. Field application of the suggested scheme showed that the convergence was controlled to within an acceptable level throughout the entire period of excavation of the lower bench. The experiences of controlling excessive squeezing deformation and optimisation of the support scheme for rock strata in a high geo-stress environment provide a reference for similar projects in the presence of soft rocks.